2019
DOI: 10.1021/acs.est.8b06967
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nitrophenolic Byproducts during Heat-Activated Peroxydisulfate Oxidation in the Presence of Natural Organic Matter and Nitrite

Abstract: Sulfate radical (SO4 •–)-based advanced oxidation is a viable in situ remediation technology for degrading organic contaminants in the subsurface. In this study, we demonstrated that SO4 •– could induce the activation of nitrite, an anion commonly present in the subsurface environment, leading to the formation of nitrophenolic byproducts. Fourier-transform infrared spectroscope and 15N nuclear magnetic resonance analysis revealed that the inorganic nitrite was incorporated into natural organic matter (NOM) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 72 publications
1
64
0
Order By: Relevance
“…The occurrence of nitrate and nitrite in water and wastewater opens up the additional possibility for nitroaromatic compounds to be formed also in the framework of photochemical processes for water treatment, where radiation is often provided by UV lamps and where the aromatic substrates may occur either as contaminants, or as components of the natural organic matter. In some cases, nitrite may even occur together with strong oxidising agents intended for pollutant degradation, yielding nitroderivatives upon oxidation to • NO 2 [ 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of nitrate and nitrite in water and wastewater opens up the additional possibility for nitroaromatic compounds to be formed also in the framework of photochemical processes for water treatment, where radiation is often provided by UV lamps and where the aromatic substrates may occur either as contaminants, or as components of the natural organic matter. In some cases, nitrite may even occur together with strong oxidising agents intended for pollutant degradation, yielding nitroderivatives upon oxidation to • NO 2 [ 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…•−based AOP with NO 2 − : (1) nitration of phenol or 4hydroxybenzoic acid can be directly initiated by • NO 2 through hydrogen abstraction to form phenoxy radicals, which further react with another • NO 2 to generate nitro compounds; 23,24 and (2) chlorophenols are first attacked by SO 4…”
Section: •−mentioning
confidence: 99%
“…Previous studies have reported that nitrophenolic byproducts are significantly generated during phenolic compound degradation by thermally activated PDS oxidation in the presence of NO 2 – . The following two pathways of nitro compound formation have been proposed during the SO 4 •– -based AOP with NO 2 – : (1) nitration of phenol or 4-hydroxybenzoic acid can be directly initiated by • NO 2 through hydrogen abstraction to form phenoxy radicals, which further react with another • NO 2 to generate nitro compounds; , and (2) chlorophenols are first attacked by SO 4 •– to form phenoxy radicals, which then combine with • NO 2 to form chloronitrophenols . However, both pathways are speculated and lack direct experimental evidence.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the reports in the literature that nitrogen-containing by-products are toxic and carcinogenic to humans, 65,66 the change regularity in the acute toxicity of BPA in the UV/NO 3 − process was investigated (Fig. 11).…”
Section: Resultsmentioning
confidence: 99%